Zoning as a tool of land management. (November 2019) - Komarov, S I; Antropov, D V; Varlamov, A A; Galchenko, S A; Zhdanova, R V
Abstract: The article describes the zoning of Russia as part of strategic planning. The draft project "Spatial Development Strategy" developed by the Ministry of Economic Development is analyzed. The composition of the zones of this project is compared with authors' zoning results based on land and property development indicators and influencing factors. The conclusion about poor accounting of land resources and land relations in strategic planning was drawn.